Co nanoparticles and ZnS decorated N, S co-doped carbon nanotubes as an efficient oxygen reduction catalyst in zinc-air batteries. (23rd August 2021) - Huang, Kexin; Zhang, Wanqing; Devasenathipathy, Rajkumar; Yang, Zhongyun; Zhang, Xiaoxia; Wang, Xiaoqu; Chen, Du-Hong; Fan, Youjun; Chen, Wei
Abstract: The economical, efficient and durable oxygen reduction catalysts facilitate the enhancement of electrochemical energy devices competitiveness towards widespread applications. In view of this, we provide an innovative sulfuration inducing method for the synthesis of ZnS and cobalt nanoparticles decorated N, S co-doped CNTs (ZnS/Co-NSCNTs) catalyst. S introduced into the zinc-based zeolitic imidazolate frameworks (ZIF-8) and cobalt-based zeolitic imidazolate frameworks (ZIF-67) precursors via pyrolysis, and induced the generation of ZnS/Co-NSCNTs have been confirmed by XRD, SEM, TEM, and XPS techniques. The key features including activity sites, transfer channels and adsorption energy back up the excellent electrocatalytic activity of the as-prepared ZnS/Co-NSCNTs towards oxygen reduction reactions (ORR). ZnS/Co-NSCNTs additionally exhibited a positive half-wave potential of 0.871 V (vs. RHE) with improved current density towards ORR. In alkaline medium, ZnS/Co-NSCNTs catalyst displayed a high tolerance towards methanol and an excellent long-term cycling stability. The observed onset potential for our prepared ZnS/Co-NSCNTs catalyst is analogous with the commercially available noble metal catalysts. Also, ZnS/Co-NSCNTs catalyst as a cathode in zinc-air battery displayed an enhanced electrochemical performance with a highly specific capacity of 750.1 mAh g −1, outstanding cycling stability, and high rate behavior. This work provides a new approach for the construction of stable low-cost alternative air-cathode catalysts for other energy conversion and storage applications. Highlights: Sulfuration induced ZIF-8/ZIF-67 to N and S co-doped carbon tube loaded ZnS and Co. ZnS/Co-NSCNTs own rich transfer channels, activity sites, and low adsorption energy. ZnS/Co-NSCNTs exhibit superb ORR activity and stability in Zn-air battery.